PENGEMBANGAN BAHAN AJAR TEKS CERITA RAKYAT SUMATRA UTARA BERBASIS CANVA UNTUK SISWA SEKOLAH MENENGAH PERTAMA - Riska Pandea Salsabila; Diah Kusyani; Andi Syahputra Harahap (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aims to develop Canva-based instructional materials for North Sumatran folklore texts for junior high school students by applying the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The analysis stage involved identifying students’ needs and the applicable curriculum, which revealed that folklore materials in textbooks tend to be monotonous and less engaging for students. During the design stage, the researcher developed a student learning module equipped with intrinsic and extrinsic elements, interactive exercises, and visual displays featuring a modern ethnic theme characteristic of North Sumatra. The module was developed using Canva, incorporating animations and quizzes to enhance student engagement. The material expert validation results showed a feasibility percentage of 90% (very feasible category), while media expert validation reached 91.2% (very feasible category). Teacher responses to the instructional materials were also highly positive, with an average score of 90.4%, indicating that the module is attractive, easy to use, and relevant to the needs of 21st-century learning. Based on these results, it can be concluded that the Canva-based North Sumatran folklore instructional materials are feasible to be used as an innovative learning medium that not only enriches students’ understanding of local culture but also fosters learning interest through the integration of digital technology in Indonesian language learning.